(3JWhjQ Jbjje GdCOGA GdJQHhj ddeOQSI GddHfGfjI ebGQHI dHfGA eYGjjQ GdJbjje GdPGJj hELQGAGJg hJMPjQgG aj hGbY GdSjGb GdeMdjs - (3cQGej, QjeI s; (3QRb Gddg, OdGds ((3HjQhJs (3GdLeYjI GdYQHjI dYdhe GdGLJeGYs, 2014)
(3JHQR GdETcGdjI GdJj JJfGhdgG gPg GdOQGSI aj GdJbhje GdJQHhj aj GdHdOGf GdYQHjI YeheG, haj dHfGf NUhUG, hJcef aj eOi ehGAeI GdeYGjjQ GdeYJeOI YGdejG dJWdYGJ GdeLJeYGJ hbjegG hXQhagG GdeMqdjI(B. (3ETJedJ gPg GdOQGSI Ydi eQMdJjf, JJfGhd GdChdi JWhjQ NWI Jbhje PGJj JYJeO ebGQHI GdJbhje GdJTGQcj hJTed COhGJ gPG GdJbhje hBdjGJ ELQGFg, hJMGhd GdKGfjI JWHjb gPG GdJUeje aj EMOi GdeOGQS GdJLQjHjI(B. (3hJSYi GdOQGSI HPdc dGbJQGM ebGQHI JDOj Edi JWhjQ egGQGJ GdJbhje dOi CaQGO GdeLJeY GdeOQSj, hJMhjd HjFI GdeOQSI Edi (B"(3eDSSGJ JYqdejI(B". (3EYJeOJ GdOQGSI JLeYG ef JLqeYGJ GdeOGQS GdcGKhdjcjI, EMOi eDSSGJ GdbWGY GdNGU aj dHfGf, hbO Jqe GNJjGQ YjfI ef (B55 (3TNUG ef CYVGA gjFI GdJOQjS aj SJ eOGQS KGfhjI(B. (3hbO Jqe GdJhUd Edi JbOje NWI dJbhje GdCOGA GdJQHhj JSGYO Ydi JMhjd eLJeY GdeOQSI Edi (B"(3eLJeY JYde egfqj(B" (3JShO ajg KbGaI GdJbjje hGdeTGQcI ef CLd GdJWhjQ, hGdJYGhf hGdMhGQ(B. (3hNJeJ GdhQbI HefGbTI ddebGQHI GdeJHYI dEYOGO GdNWI ef MjK CKQgG aj cjajI JWhjQ eYGjjQ GdJbhje, hEecGfjI GdGSJaGOI efgG dJWhjQ fXGe GYJeGO eMdj jLeY Hjf GdCOHjGJ GdYGdjeI hhGbY GdeOGQS GdeMqdjI(B.s
(3GdfhY (B: (3ebGds
Keywords: Evaluation Institutionnelle; Institutional assessment Socio-Cultural Milieu; Milieu Socio-Culturel; (3GdJbjje GdeDSSj GdhSW GdKbGaj GdGLJeGYjs